Physical and Electrochemical Properties of Some Phosphonium-Based Ionic Liquids and the Performance of Their Electrolytes in Lithium-Ion Batteries. Issue 8 (16th May 2017) - Salem, Nuha; Zavorine, Serguei; Nucciarone, Donato; Whitbread, Kristina; Moser, Mike; Abu-Lebdeh, Yaser
Abstract : In this work, three ionic liquids with two different cations and two different anions: trimethyl propyl phosphonium bis-fluorosulfonyl imide (P1113 FSI), trimethyl isobutyl phosphonium bis-fluorosulfonyl imide (P111 i 4 FSI) and trimethyl isobutyl phosphonium bis-trifluoromethylsulfonyl imide (P111 i 4 TFSI) have been characterized and evaluated as electrolytes in lithium ion half-cells. It is found that ionic liquids with FSI − anion have superior properties over their TFSI − counterparts and those with the smaller cation, P1113, have better conductivity and viscosity. The two ionic liquids with FSI anion, P1113 FSI and P111 i 4 FSI, are liquid at room temperature and show high conductivities and low viscosities, reaching 10.0 mS/cm and 30 cP at room temperature for P1113 FSI. They also exhibit electrochemical windows higher than 5 V and thermal stability exceeding 300°C. Mixing the ionic liquids with 0.5 M LiPF6 increases viscosities, lowers conductivities but improves electrochemical cathodic stability. The electrolyte mixtures have been evaluated in graphite/Li half cells, Li/LiFePO4 and Li/LiMn1.5 Ni0.5 O4 at C/12 for 100 cycles and at different rates: C/6, C/3, C and 2C for rate capabilities. Battery testing shows that unlike their TFSI − counterparts both ionic liquids with FSI − anion perform well with graphite anode and LiFePO4 cathode but fail with the higher voltage LiMn1.5 Ni0.5 O4 cathode.